2020
DOI: 10.1101/2020.11.10.20228759
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parents’ Likelihood to Vaccinate Their Children and Themselves Against COVID-19

Abstract: BackgroundVaccination against COVID-19 will likely involve children in order to mitigate transmission risks in community settings. Successful implementation of COVID-19 immunization in the United States may hinge on factors associated with parents’ likelihood of immunizing their children and themselves.MethodsWe fielded a national household survey in English and Spanish from June 5-10, 2020 (n=1,008). Parents were asked about their likelihood of immunizing their children and themselves against COVID-19. We fit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 6 publications
0
18
2
Order By: Relevance
“…In a study conducted in a paediatric emergency department, the child's age, receipt of routine vaccinations, having the child or a parent having been vaccinated against the flu in the previous year, and worrying about their child being infected COVID‐19 were found to be associated with increased parents’ willingness to permit administration of the COVID‐19 vaccine 9 . In another study, increased parental age, male gender, being married, being education to college level or higher and higher income were associated with willingness to allow their children to receive the COVID‐19 vaccine 13 . A study evaluating vaccine hesitation and rejection in Italy identified economic hardship as a determinant of vaccine hesitation.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…In a study conducted in a paediatric emergency department, the child's age, receipt of routine vaccinations, having the child or a parent having been vaccinated against the flu in the previous year, and worrying about their child being infected COVID‐19 were found to be associated with increased parents’ willingness to permit administration of the COVID‐19 vaccine 9 . In another study, increased parental age, male gender, being married, being education to college level or higher and higher income were associated with willingness to allow their children to receive the COVID‐19 vaccine 13 . A study evaluating vaccine hesitation and rejection in Italy identified economic hardship as a determinant of vaccine hesitation.…”
Section: Discussionmentioning
confidence: 93%
“…9 In another study, increased parental age, male gender, being married, being education to college level or higher and higher income were associated with willingness to allow their children to receive the COVID-19 vaccine. 13 A study evaluating vaccine hesitation and rejection in Italy identified economic hardship as a determinant of vaccine hesitation. A low level of education emerged as an indicator of complete vaccine rejection without affecting vaccine hesitations.…”
Section: Discussionsmentioning
confidence: 99%
See 2 more Smart Citations
“…International Publisher [10]. In addition, certain susceptible populations have been suggested as inapplicable recipients of the vaccine, including women who are pregnant or within the lactation period and patients with severe basic illnesses or malignant tumors.…”
Section: Ivyspringmentioning
confidence: 99%